412 Polytetrafluoroethylene(PTFE) Pledgets Masquerading As A Pseudo-Aneurysm Of Left Ventricle Apex. A Case Report. (12th October 2021) - Moawad, N; Asopa, S; Lloyd, C
Abstract: Background: TransCatheter Aortic Valve Implantation (TAVI) is now established as an alternative for open aortic valve replacement in high-risk patients with severe calcified degenerative aortic stenosis. Case presentation: Here we report a case of a 78 tears old female patient who presented six months following transapical TAVI with a pulsatile mass over the left anterior mini thoracotomy wound. Transthoracic echocardiography showed suspicion of a left ventricular apical aneurysm with no evidence of free pericardial fluid.Contrast enhanced CT reported a large pseudo-aneurysm arising from the apex of the left ventricle extending through the left anterior thoracic wall. She was scheduled for emergency surgical exploration via median sternotomy. Upon median sternotomy there were dense pericardial adhesions limiting the mobilization of the heart specially the apex, which necessitated establishment of cardiopulmonary bypass. The heart was arrested, and the dissection was completed. The cavity in connection with the ventricular apex had purulent contents and the site of the TAVI ventriculotomy was secure with the PTFE pledgets in place with no evidence of leakage. Samples of the cavity fluids had pus cells, but no organisms were grown. The patient made an uneventful recovery and was discharged home 6 days postoperatively. Discussion: PTFE pledgets are frequently used in cardiac surgery to support surgical closure. These pledgets on a contrast enhanced CT scan can make it difficult to correctly diagnose and may mimic anastomotic leaks as both give similar hyper-dense appearance on contrast enhanced CT scan